Role of dietary zinc in heat-stressed poultry: A review - Şahin, Kazım; Şahin, Nurhan.; Küçük, Ömer; Hayirli, A.; Prasad, A. S. (Elsevier, 2009)
High ambient temperatures compromise performance and productivity through reducing feed intake and decreasing nutrient utilization, growth rate, egg production, egg quality, and feed efficiency, which lead to economic losses in poultry. Environmental stress also leads to oxidative stress associated with a reduced antioxidant status in the bird in vivo, as reflected by increased oxidative damage and lowered plasma concentrations of antioxidant vitamins (e. g., vitamins E, A, and C) and minerals (e. g., Zn). Zinc has an important role in numerous biological processes in avian and mammalian species. For instance, Zn is an essential component of many enzymes, and it has both structural and catalytic functions in metalloenzymes. Furthermore, dietary Zn is required for normal immune function as well as proper skeletal development and maintenance. One of the most important functions of Zn is related to its antioxidant role and its participation in the antioxidant defense system. This work compiles past and present information about the role of Zn in heat-stressed poultry health.
Keywords: heat stress; zinc; poultry